2013
DOI: 10.1186/1756-0500-6-239
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Cosmos caudatus (ulam raja) on dynamic and cellular bone histomorphometry in ovariectomized rats

Abstract: BackgroundCosmos caudatus is a local plant which has antioxidant properties and contains high calcium. It is also reported to be able to strengthen the bone. This report is an extension to previously published article in Evidence Based Complementary and Alternative Medicine (doi:10.1155/2012/817814). In this study, we determined the effectiveness of C. caudatus as an alternative treatment for osteoporosis due to post-menopause by looking at the dynamic and cellular paramaters of bone histomorphometry.MethodsFo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Results showed that the extract increased double-labelled surface, mineral appositional rate, osteoid volume and osteoblast surface, supporting its role in bone protection. It was also reported that supplementation of C. caudatus can prevent the increase of interleukin-1, pyridinoline and bone resorption in ovariectomized rats 83 . In a follow-up study, C. caudatus extract (500 mg/kg) was found to enhance fracture healing in ovariectomized rats with fractured tibia 84 .…”
Section: Anti-osteoporosismentioning
confidence: 92%
See 2 more Smart Citations
“…Results showed that the extract increased double-labelled surface, mineral appositional rate, osteoid volume and osteoblast surface, supporting its role in bone protection. It was also reported that supplementation of C. caudatus can prevent the increase of interleukin-1, pyridinoline and bone resorption in ovariectomized rats 83 . In a follow-up study, C. caudatus extract (500 mg/kg) was found to enhance fracture healing in ovariectomized rats with fractured tibia 84 .…”
Section: Anti-osteoporosismentioning
confidence: 92%
“…The effectiveness of C. caudatus in the bone protection of post-menopause osteoporosis has been studied in rats 81 . Four groups of eight female rats were ovariectomized, and treatments of 1% calcium and 500 mg/kg of C. caudatus extract were given six days a week for eight weeks.…”
Section: Anti-osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18] Ulam raja can also stimulate bone formation and improve the dynamic and cellular bone histomorphometry parameters. [19,20] A recent report indicated that Ulam raja supplementation in mice can lead to extrahepatic organs protection from xenobiotic and oxidative injury. [21] However, this health-enhancing salad is no longer consumed frequently with rice due to the changes in the eating behavior of society, especially due to the influence of Western dietary pattern among younger generation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Ovariectomy causes loss of bone volume, decrease in trabecular number, and increase in trabecular separation in ovariectomized rats. [ 19 ] However, in both the groups of ovariectomized rats supplemented with 500 mg/kg C. caudatus aqueous extract and with 1% calcium for 8 weeks, an ameliorating effect was observed on bone volume, number, and separation by restoring the bone structural parameters to the normal level. [ 19 ] Surprisingly, a superior effect of C. caudatus on trabecular separation and trabecular number was observed as compared to calcium 1% treatment in rats.…”
Section: Resultsmentioning
confidence: 99%